Chiral Perovskites: Promising Materials toward Next‐Generation Optoelectronics. Issue 39 (6th August 2019) - Dong, Yuze; Zhang, Yupeng; Li, Xinyue; Feng, Yaqing; Zhang, Han; Xu, Jialiang
Abstract: Halide perovskites have emerged as a type of extremely promising material for their diverse chemical and electronic structures along with their brilliant optoelectronic properties. The introduction of chirality into perovskite scaffolds, generating a novel concept of chiral perovskite materials, offers an immense step forward toward the development of smart optoelectronic and spintronic materials and devices. The present Review summarizes recent advances in such an emerging field regarding the design and construction of chiral perovskite materials, along with their optoelectronic performances. In addition, an outlook of future challenges as well as the potential significance of the chiral perovskite family on the optical communication is proposed. Abstract : The introduction of chirality into the perovskite scaffolds, leading to the generation of chiral perovskite materials, is an immense step forward toward the development of smart optoelectronic and spintronic materials and devices. Here, the recent advancements in chiral perovskites including their design and construction along with the optoelectronic properties are reviewed, and the future research directions to overcome current challenges are also proposed.